Association between complementary factor H Y402H polymorphisms and age-related macular degeneration in Chinese: Systematic review and meta-analysis - Quan, Yan-Long; Zhou, Ai-Yi; Feng, Zhao-Hui (International journal of ophthalmology, 2012)
AIM: Age-related macular degeneration (AMD) is the leading cause of blindness in the developed world and complement factor H (CFH) polymorphism has been found to associate with the AMD. To investigate whether the Y402H variant in CFH is associated with AMD in Chinese populations, a systematic review and meta-analysis were performed to estimate the magnitude of the gene effect and the possible mode of action. · METHODS: A meta-analysis was performed using data available from ten case-control studies assessing association between the CFH Y402H polymorphism and AMD in Chinese populations involving 1538 AMD. Data extraction and study quality assessment were performed in duplicate. Summary odds ratios (ORs) and 95% confidence intervals (CIs) an allele contrast and genotype contrast were estimated usingfixed- effects models. The Q-statistic test was used to assess heterogeneity, and Funnel plot was used to evaluate publication bias. · RESULTS: Seven of ten case-control studies were neovascular AMD, and few studies came from west and north of China. There was strong evidence for association between CFH and AMD in Chinese population, with those having risk allele C 2.35 times more likely to have AMD than subjects with T allele. Evidence of publication bias was not observed in our meta-analysis. · CONCLUSION: This meta-analysis summarizes the strong evidence for an association between CFH and AMD in Chinese and indicates each C allele increasing the odds of AMD by 2.33-fold.But more evidences about the relation between CFH polymorphism and different type of Chinese AMD from various district were needed.